2019
DOI: 10.1186/s13104-019-4611-7
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic toxicity of low dose monosodium glutamate in albino Wistar rats

Abstract: Objective The objective of this study was to observe the effects of chronic dosing with monosodium glutamate on mortality, fertility, major organ functions and histology in albino Wistar rats. Results 6 male and 6 female rats (age 6 weeks) were bred in a cage, feeding on standard growers’ mash, with monosodium glutamate added (120 mg/kg/day). 12 corresponding breeding rats (on standard feed without MSG) were controls. Chronic dosing with monosodium glutamate in albino Wistar rats (at a dose consistent with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 35 publications
3
16
0
3
Order By: Relevance
“…The effects of MSG supplemented diet on the cockroach nymphs' survival rate presented in Figure 5 revealed that the survival rate of cockroach nymphs' decreases with increase concentration of MSG in the diet with the highest MSG dose (100 mg/g) having the lowest rate (77%) of survival when compared with the control. The trend obtained in this study agrees with earlier report whereby high dose of MSG led to a reduction in survival rate of rats (Josiah et al, 2019).…”
Section: An Established Indirect Methods For Measuring Oxidative Stresssupporting
confidence: 93%
“…The effects of MSG supplemented diet on the cockroach nymphs' survival rate presented in Figure 5 revealed that the survival rate of cockroach nymphs' decreases with increase concentration of MSG in the diet with the highest MSG dose (100 mg/g) having the lowest rate (77%) of survival when compared with the control. The trend obtained in this study agrees with earlier report whereby high dose of MSG led to a reduction in survival rate of rats (Josiah et al, 2019).…”
Section: An Established Indirect Methods For Measuring Oxidative Stresssupporting
confidence: 93%
“…AST exhibiting 16.28%, 34.57% and 42.08% increase in low, mid and high MSG induced group when compared to control animals concludes that hepatic cellular damage caused by MSG. The considerable increase in ALT and ALP in monosodium induced groups were more or less similar to AST levels which reinforces that hepatocellular leakage of those enzymes due to the liver injury caused by MSG [10]. The analysis of AST and ALT enzymes for groups induced with MSG (low, mid, and high doses) displays possible damage to liver cell membrane and cytosol due to monosodium induced oxidative stress which may would have triggered the hepatocytes to become leaky, releasing those liver enzymes in serum [7,17].…”
Section: Discussionsupporting
confidence: 67%
“…The Liver is one of the primary organs of the human body involved in detoxification and metabolism. Earlier studies show that administration of MSG in animals causes hepatotoxicity by altering liver enzymes such as Alanine Aminotransferase, Aspartate Aminotransferase, γ-glutamyltransferase, and bilirubin in serum as well as causing oxidative stress in the liver by depleting endogenous antioxidants such as Catalase, Superoxide dismutase and reduced glutathione [7][8][9][10]. Even MSG is most commonly employed to induce obesity models in animal studies as it modifies the lipid profile in biological systems [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Glutamate is an excitatory neurotransmitter, and mostly the excitotoxicity is mediated by NMDA receptors as in neuroinflammatory demyelinating and amyotrophic lateral sclerosis. MSG in ready-made foods has also been linked to nephrotoxicity, hepatotoxicity, asthma, urticaria, neoplastic cell growth, and differentiation [ 41 ]. MSG as a food additive also causes angioedema and urticaria in randomized controlled trials in humans [ 36 , 42 ].…”
Section: Msg Used As a Flavor-enhancing Agent Causes Systemic Anomaliesmentioning
confidence: 99%